The effects of acute malathion exposure on the cerebellum of female rats The effects of acute malathion exposure on the cerebellum of female rats - Kasim, Fazlina (2010)
Malathion is an organophosphate pesticide which is used for agricultural pest control and dengue control in Malaysia. As pesticides use is on the rise to augment agricultural productivity in Malaysia, there is also evidence of an increasing trend of pesticide poisoning. Malathion irreversibly inhibits acetylcholinesterase resulting in an impairment of numerous body functions. Even though there is sufficient information about the neurotoxicity of organophosphates , there is limited information on the effects of malathion on the cerebellum. This study is conducted to determine the effects of acute malathion exposure on the estimated total number ofPurkinje cells; and the thickness of the granular and molecular layers in the cerebellum of rats. Ten adult female Wistar rats were administered 250 mg/kg intraperitoneal malathion (corresponding to 0.2 of malathion's LD50) daily for seven consecutive days. In the control group, ten rats received equivalent volumes of 0.9% sodium chloride instead. Body weight was monitored daily. Twenty-four hours after the seventh dose of malathion, the rats were sacrificed and their cerebellum taken for analyses. Each cerebellum was sampled systematically and randomly by applying the fractionator method and stained with cresyl fast violet. Subsequently, Purkinje cells nucleoli were counted to obtain an estimation of the total number of Purkinje cells in each cerebellum. The thicknesses of the granular and molecular layers were measured using an image analyser. Data obtained were analysed using the Statistical Package for Social Science, version 12. Rats exposed to malathion showed significant deficits in body weight compared to rats in the control group (t = 4.27, p < 0.001 ). There is no statistically significant difference in the estimated total number of Purkinje cells between the malathion-exposed group and the control group. The thickness of the granular and molecular layers was also not significantly different between the two groups. It is concluded that the dose of malathion used in this experiment did not have any significant effect on the total numbers of Purkinje cells and the thickness of the granular and molecular layers in the cerebellum of rats. Further studies on the effects of malathion on the cerebellum will be conducted by applying a higher dose of malathion or a longer duration of malathion exposure.